Der Wirkungsgrad von Training - Beneke R; Leithäuser RM (Deutsche Zeitschrift für Sportmedizin)
The hypotheses that a) a positive correlation between running oxygen uptake (VO2run) and peak oxygen uptake (VO2peak) is caused by a higher caloric equivalent and/or more reliance on anaerobic metabolic energy in subjects with lower VO2peak and that b) the energy cost per meter increases with relative intensity related to VO2peak were tested. Twenty-nine males (meanSD age: 24.42.7yrs; height: 179.05.6cm; body mass: 74.56.8kg; VO2peak: 51.55.2ml kg-1 min-1) ran at 2.6 and 3.0m s-1. VO2run, oxygen uptake per meter distance (CVO2), energy cost per meter distance based on respiratory measures and indirect calorimetry (CAER), and net increase in blood lactate concentration (CANAER), as well as total C (CTOT=CAER+CANAER) were analyzed. Ad a) VO2run and CVO2 were positively, and CANAER negatively interrelated with VO2peak (all p<0.05). CTOT was independent of VO2peak. Ad b) CVO2 was independent of relative intensity related to VO2peak, whilst CAER, CANAER and CTOT increased with relative intensity (all p<0.05). The frequently observedpositive interrelationship between VO2run and VO2peak reflects less aerobic carbohydrate combustion and less reliance on anaerobic glycolysis in fitter subjects with higher VO2peak. Additionally, running economy decreases with increasing relative intensity.KEY WORDS: Terrestrial Locomotion, Human, Speed, Aerobic, Anaerobic